Antiendothelial cell antibodies in vasculitis and connective tissue disease. Issue 12 (28th March 2006) - Belizna, C; Duijvestijn, A; Hamidou, M; Cohen Tervaert, J W
Abstract : Antiendothelial cell antibodies (AECA) are a heterogeneous family of antibodies reacting with endothelial cell antigens. These antibodies are found in various diseases and recognise several antigen determinants. Different pathophysiological effects have been observed in in vitro experiments, which include direct or indirect cytotoxicity and endothelial cell apoptosis. Furthermore, some AECA activate endothelial cells, resulting in increased leucocyte adhesiveness, activation of coagulation and vascular thrombosis. In animal models, it has been shown that AECA could promote vascular damage. Neither the endothelial cell antigens nor their precise role in the pathogenecity of different diseases in which AECA are found is well characterised. Nowadays, it is not known whether AECA are an epiphenomenon accompanying vascular injury or whether they are pathogenic. It is controversial whether fluctuations in AECA titres are associated with disease activity during follow-up studies. This review summarises the present knowledge about AECA, AECA antigens and their potential role in the pathogenecity of vasculitis and connective tissue diseases.